+0  
 
0
46
2
avatar+4407 

Help

NotSoSmart  Nov 21, 2018

Best Answer 

 #1
avatar+3190 
+2

\(f(x)=(x+3)(x-5)\)

Rom  Nov 21, 2018
 #1
avatar+3190 
+2
Best Answer

\(f(x)=(x+3)(x-5)\)

Rom  Nov 21, 2018
 #2
avatar+656 
+2

Explanation: If the graph intersects the x-axis, then y must equal 0. We have the equation , \(f(x) = y\)which becomes \(f(x) = 0\). The function will be equal to 0 when the opposite of\(x\) is added to it (when added, cancels out each other to make 0). When x = -3, we can add 3 to make f(x) = 0, and when x = 5, we can subtract 5 to make f(x) = 0. We have our equation for f(x): \(\boxed{f(x) = (x+3)(x-5)}\).

 

Hope this helps,

- PM

PartialMathematician  Nov 22, 2018

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.